(untitled) (INNOVATIVE ECONOMY, 2021)
Felenchak Yu.B., Grafska O.I., Pidvalna O.H. TOURISM AS A SPHERE OF HUMAN SOCIALIZATION: ESSENCE AND SCIENTIFIC APPROACHES Purpose. The purpose of the article is to analyze scientific approaches to the interpretation of tourism as a sphere of human socialization and substantiation of its essence from the standpoint of social economy and politics. Methodology of research. The following research methods are used to achieve such purpose: scientific literature analysis is used to study approaches to understanding the essence and structure of the concept of "tourism", its social nature; generalization and synthesis are used to substantiate the conceptual foundations of tourism research as a sphere of human socialization. Findings. Scientific approaches in both foreign and Ukrainian science to the definition of "tourism" in terms of social economy and politics are analyzed. Based on the results of the analysis, a conceptual model of "tourism" concept interpretation as a functional unity of economic, consumer, social and cultural approaches taking into account the social accessibility of tourist services to different categories of consumers is formulated. It is established that a characteristic feature of modern tourism is a clear social orientation, which positions tourism as a special social sphere of the economy. Active development of tourism is able to eliminate the disparities of social and economic development, contribute to increasing the productivity of traditional farming, preservation of cultural heritage and authenticity of the regions. Originality. Theoretical and methodological principles of tourism research from the standpoint of social economy have been improved. Scientific approaches to the definition of "tourism" have been further developed. Practical value. The results of the study can be used in the practice of public management of tourism development, strategic planning, and educational and scientific sphere, in particular, can be the basis for further research on the socialization of tourism. Key words: tourism, socialization of the economy, socialization of tourism, definition, scientific approaches, social accessibility.